Gone - Gardner, Lisa. (New York : Random House Large Print in association with Bantam, 2006)
When his partner and lover, Rainie Connor, vanishes during her investigation into the case of a missing foster child, private detective Pierce Quincy enlists the aid of his daughter Kimberly, a rookie FBI agent, to uncover the truth.
Keywords: Missing persons -- Fiction; Kidnapping victims -- Fiction; Government investigators -- Fiction; Separated people -- Fiction; Large type books; Oregon -- Fiction; Suspense fiction; Domestic fiction